(untitled) (Current Horticulture, 2024)
Seven isolates of blue mould fungi (Penicillium italicum), causing blue mould rot on orange (Citrus reticulata Blanco) isolated from Jobner region exhibited variable growth on artificial culture media (PDA). The PI-1 appeared as dark green centre with white periphery. The other isolates had different colony characters with green to light blue centre surrounded by cottony to profuse colony peripheries. The disease intensities of blue mould isolates were also variable. The PI-1, PI-2 and PI-3 were at par, while maximum intensity (57.76 %) was recorded in PI-1 and minimum (21.12 %) in PI-7.